ORGANOLEPTIC QUALITY OF BALI BEEF IN DIFFERENT COMERCIAL CUT - N. N. S., Apriyanti; Sriyani, N.L.P; Putra, I G. A. A. (Jurnal Peternakan Tropika; Vol 10 No 1 (2022): Vol. 10 No. 1 Tahun 2022; January - april, 2022)
This study aimed to determine the organoleptic quality of bali cattle carcass in different commercial cut.  This study was conducted at Laboratory of Animal Products Technology and Microbiology, Faculty of Animal Husbandry,  Udayana University,  for two months,  from August to September 2020.  This study used a completely randomized design (CRD) with three meat samples comparison assessed by 15 semi-trained panelists.  The three comparisons were the passive muscle in the carcass comercial cut short loin  (P1),  semi-active muscle in the carcass comercial cut round  (P2) and active muscle in the carcass comercial cut hind shank  (P3).  The variables observed were an organoleptic tests,  including color,  flavour,  texture,  taste,  and overall acceptance.  The results showed that the difference in locations of three bali cattle carcass on organoleptic had a significant influence (P<0,05) on the colors,  texture and overall acceptance.  However, there was no significant influence (P>0,05) on flavour and taste.  The conclusion of this study was passive muscle becomes the most favored and accepted organoleptic quality of bali cattle by the panelists based on the difference in locations of passive muscle,  semi-active muscle ,   and active muscles.  It is seen from the acceptance assessment of the panelists on the colors,  flavour,  textures,  taste and overall acceptance variables.   Keywords: Organoleptic test, bali cattle beef, comercial cut